Provisional Application of Treaties and Other Topics: The Seventy-Second Session of The International Law Commission. Issue 4 (October 2021) - Murphy, Sean D.
Abstract : The International Law Commission (ILC) held its seventy-second session from April 26 to June 4 and from July 5 to August 6, 2021 in Geneva, under the chairmanship of Mahmoud Hmoud (Jordan). This session was originally scheduled for the summer of 2020, but had to be postponed due to the outbreak of the COVID-19 pandemic. The pandemic continued in 2021 to present health risks and travel difficulties for certain members; consequently, the Commission for the first time in its history held its session in a hybrid manner, with many members physically present in Geneva, while others participated online by means of Zoom. That approach required certain adjustments to the Commission's methods of work, but allowed the Commission to move forward in addressing the several topics on its current program of work.